Charge accumulation and electron transfer kinetics in Geobacter sulfurreducens biofilms - Bonanni, Pablo Sebastian (2012)
Electroactive bacteria can use a polarized electrode as final electron acceptor, allowing the use of electrochemical techniques for a very accurate quantification of its respiration rate. Biofilm cell respiration has been recently demonstrated to continue after the interruption of electrode polarization since these bacteria can store electrons in the haem groups of exocytoplasmic cytochromes. Interestingly, it has been shown that when the electrode is connected again, stored electrons can be recovered as a current superimposed to the basal steady state current produced by biofilm respiration. This work presents a model for the biofilm-catalysed electron transfer mechanism that reproduces the current profile obtained upon electrode reconnection. The model allows the estimation of kinetic parameters for internalization of the reduced substrate by the cells and the subsequent reduction of cell internal cytochromes, the electron transfer to mediators in the exterior of the cell, charge transport across the biofilm matrix to the electrode through fixed mediators and, finally, the oxidation of cytochromes at the biofilm/electrode interface. Based on these estimates, the distribution of stored charge within the biofilm can also be calculated. The results indicate that the processes involved in electron transfer from acetate to internal cytochromes represent the main limitation to current production, showing that both electron transport through the matrix of cytochromes and interfacial electron transfer are orders of magnitude faster than this process. Stored charge, on the other hand, is an order of magnitude higher inside the cells compared with that in the conductive matrix, suggesting that internal cytochromes are approximately ten times more abundant inside the cells than in the conductive matrix.